Diversity and characterization of fungi and its relevance - and K.V.B.R. TILAK, C. MANOHARACHARY*, I.K. KUNWAR (Indian Phytopathology, 2013)
Fungal diversity is an important element in nature which not only monitors the environment but is also important in agriculture, medicine, pharmaceuticals, industry, food, technology and in other biotechnological aspects. Fungi are known to colonize diversified habitats and multiply in nature. One third of world’s fungal diversity exists in India. However fungal taxonomists are dwindling day by day posing a threat for identification of the hidden fungal wealth. Some fungi have also become endangered and require attention of mycologists to conserve them.